Food Servicing Characteristics Of The Accommodation Products As Deal-Breakers Of Consumer Purchasing Behaviors (Journal of Namibian Studies : History Politics Culture, 2023)
Customers' perceptions of value have a direct impact on their overall experience and behavioral intentions of purchasing a product. Analyzing customers' intentions and motivations behind their food service experiences can shed light on the factors that influence their decision to visit specific establishments, their likelihood of revisiting, and their willingness to recommend the place to others. The purpose of this study was to explore the characteristics of food servicing and how it could influence customers to purchase accommodation. This study employed qualitative analysis to explore the experiences of customers in availing an accommodation. Customers (n=32) were interviewed about their experiences seeking information on which characteristics served as purchasing deal-breakers for them. The findings reveal that customers prioritize high-quality and appealing food products and menu offerings (healthy, local food), service quality (attitudes and behavior of the service crew), area (overall atmosphere, furniture), and pricing (discounts, low price points). These characteristics could influence their purchasing intention for an accommodation highlighting the need to meet the expectations and individual needs of the customers. These priority food servicing characteristics highlight the potential of food tourism within accommodation establishments. Understanding and addressing these factors can significantly impact consumer purchase behavior and attract more customers to the accommodation industry.